Experimental studies on thread-fixed one-side bolted T-stubs in tension at elevated temperatures. (August 2020) - You, Yang; Liu, Mei; Liu, Yuanjian; Wang, Peijun; Zhou, Shengzhan; Chen, Junxia
ABSTRACT: Tests were carried out to investigate the tensile behavior of T-stubs connected by Thread-fixed One-side Bolts (TOB) at ambient and high temperatures. A total of 25 T-stub specimens with different bolt diameters and T-stub flange thicknesses were tested. In the high temperature tests, load ratios of 0.5 and 0.75 in transient-state tests and temperatures of 500 °C and 700 °C were selected in the steady-state tests. Totally four failure modes were observed in ambient and high temperature tests, which were the bolt failure, the flange yielding, flange yielding accompanied with bolts failure, as well as the flange yielding accompanied with threads failure. Results of high temperature tests showed that the failure modes of the same bolted T-stubs would be different at different temperatures in the steady-state tests or under different load ratios in the transient-state tests. However, the unfavorable failure modes integrating threads failure did not occur in high temperature tests, which demonstrated the good applicability of TOB in a fire. In transient-state tests, bolted T-stubs under the small load ratio had better ductility and higher failure temperature. In steady-state tests, the yielding strength, the ultimate strength as well as the initial stiffness decreased with the increase of temperature. The yield strength of bolted T-stubs could also be increased through the increase of bolt diameter and flange thickness of the target T-stub. Design equations for the yield strength of T-stubs connected using TOB at high temperatures were modified. The failure modes and yielding strength of TOB connected T-stubs at elevated temperatures predicted by modified design equations agreeed well with test results. Highlights: Fire tests were carried out to investigate tensile behavior of one-side bolted T-stubs. Totally four failure modes were observed at ambient and high temperature tests. Design equations for one-side bolted T-stubs at high temperatures were modified. Predictions by proposed design equations agreed well with test results.